The chemodynamic antibacterial effect of MnOX nanosheet decorated silicon nanowire arrays. Issue 1 (22nd November 2021) - Li, Mingkang; Li, Guize; Wang, Hongwei; Yuan, Lin
Abstract : Modified manganese oxide on the surface of silicon nanowire arrays deposited on polydopamine (SN@PDA@MnO X ) had a strong chemodynamic antibacterial effect due to a significant increase in the yield of ROS within a short time. Abstract : Bacteria exist everywhere and pose a threat to human health. Reactive oxygen species (ROS), as a highly reactive chemical substance, can effectively oxidize and break lipids, DNA, protein and other bioactive molecules, leading to the death of bacteria. Modification of manganese oxide on the surface of silicon nanowire arrays deposited with polydopamine (SN@PDA@MnO X ) can significantly increase the yield of ROS in a short period of time, which provides SN@PDA@MnO X with a strong chemodynamic antibacterial effect. Both manganese ions and manganese oxides in the reaction system promote the generation of ROS, and their mechanisms of action can be synergistic with each other. The results show that SN@PDA@MnO X can achieve a 99.99% antibacterial effect by using the ROS generated by chemodynamic reactions within 1 hour. SN@PDA@MnO X has great potential as a novel antibacterial material.